Corporate Social Responsibility, Good Corporate Governance, Firm Size Towards Tax Avoidance in The Consumer Goods Industry Sector Listed on the Indonesia Stock Exchange - Hantono Hantono; Jony Jony; Rossy Pratiwy Sihombing (Universitas Dharma Wacana, 2022)
This study aims to examine the effect of Corporate Social Responsibility, Good Corporate Governance with proxy (board of commissioners, audit committee), and firm size towards tax avoidance. The population in this study is the Consumer Goods Industries listed in Indonesia Stock Exchange in 2015 until 2019. The sample was determined by the purposive sampling method and obtain 16 companies. Type of data used was secondary data obtained from www.idx.co.id and corporate websites. The method of analysis used is multiple regression analysis. The results of study show that Corporate Social Responsibility has significant effect on tax avoidance, where the significant value is 0.001 < 0.05. Good Corporate Governance with proxy (board of commissioners has significant effect on tax avoidance where the significant value is 0,032 < 0.05, audit committee does not have significant effect on tax avoidance where the significant value are 0.839 < 0.05), firm size does not have significant effect on tax avoidance, where the significant value are 0.874 > 0.05. Simultaneous test is known that the significance value (Î±) 0.009 < 0.05 with a calculated value of fcount 3,767 < ftable Â 2.76 which means that independent variables corporate social responsibility, good corporate governance with proxy by the board of commissioners and audit committee,Â firm size has a significant influence together (simultaneous) on tax avoidance. While the coefficient of determination in this study can be explained that variations of independent variables corporate social responsibility, good corporate governance with proxy by the board of commissioners and audit committees, firm size can explain the variation of variable dependent tax avoidance is 47%. While the rest (100% â€“ 47% = 53 %) is a variation of other variables that affect tax avoidance that was not found in this study.